Fumigaclavines D–H, New Ergot Alkaloids from Endophytic Aspergillus fumigatus - Xu, Jing; Song, Yong Chun; Guo, Ye; Mei, Ya Ning; Tan, Ren Xiang (Planta Medica, 2014)
Ergot alkaloids are toxins which are produced biotechnologically on an industrial scale. The chemical investigation of endophytic Aspergillus fumigatus resulted in the isolation of five new ergot alkaloids named fumigaclavines D–H (2–6), along with three known analogues, fumigaclavine C (1), festuclavine (7), and fumigaclavine A (8). Their structures were unequivocally elucidated by extensive spectroscopic analyses in association with X-ray single-crystal diffraction. Fumigaclavines D–H are interesting clavine-type ergot alkaloids featuring a reverse prenyl moiety at C-2, with 1–4, 6, and 8 bearing additional substituents, e.g., an OH or OAc group at C-9. Compounds 2, 4, and 6–8 showed a broad spectrum of antimicrobial activity against a panel of anaerobic microorganisms, of which compounds 4 and 6 were the most active against Veillonella parvula with an MIC = 16 µg/mL compared to that (0.12 µg/mL) of tinidazole, co-assayed as a positive reference.
Keywords: Aspergillus fumigates; Trichocomaceae; Cynodon dactylon; Poaceae; clavine-type ergot alkaloids; antimicrobial activity